Electoral support and militants' targeting strategies. (March 2022) - Aksoy, Deniz; Carlson, David
Militant groups that are in armed conflict with a government often coexist with political parties that have ethnic or ideological connections to them. In this article, we explore the extent to which electoral support received by militant associated opposition parties and nationally incumbent political parties influences subnational variation in militant attacks. We argue, and empirically demonstrate, that militants strategically target localities where the levels of electoral support for the opposition party and the nationally incumbent party are close in an effort to negatively influence the electoral performance of the incumbent party. To illustrate this dynamic we examine subnational data from 1995 to 2015 Turkish legislative elections and attacks organized by the Kurdish militants within the same time period. We also examine the impact of June 2015 legislative elections on militant attacks until the snap elections in November 2015. Our empirical examination shows that militants target localities where electoral support for the governing party and Kurdish opposition party is close. Moreover, increase in violence negatively influences the electoral performance of the governing party. However, it does not consistently have a significant influence on the opposition. The findings illustrate that militants strategically choose the location of their attacks based on electoral dynamics, and attacks can pose an electoral challenge to the governing party.